2018
DOI: 10.1177/0363546518779064
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Spherical Femoroplasty: Cam Overresection Leads to Inferior Functional Scores Before and After Revision Hip Arthroscopic Surgery

Abstract: Cam overresection of more than 5% of the diameter of the femoral head on the Dunn view predicts inferior clinical outcomes compared with cam underresection in this population. Furthermore, overresection predicts inferior outcomes after revision hip arthroscopic surgery and higher rates of conversion to THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(110 citation statements)
references
References 41 publications
1
109
0
Order By: Relevance
“…More commonly, excessive femoral resection has led to disruption of the native labral seal, adversely affecting hip joint biomechanics. 36 Mansor et al 11 reviewed a cohort of 120 patients (130 hips) and divided them into 3 groups (over-resected, under-resected, and neutral resected) who had a mean follow-up from index procedure of 39.6 months. The authors found that overresection greater than 5% of the femoral head diameter correlated with inferior clinical outcomes (modified Harris Hip Score) compared with the under-resected population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More commonly, excessive femoral resection has led to disruption of the native labral seal, adversely affecting hip joint biomechanics. 36 Mansor et al 11 reviewed a cohort of 120 patients (130 hips) and divided them into 3 groups (over-resected, under-resected, and neutral resected) who had a mean follow-up from index procedure of 39.6 months. The authors found that overresection greater than 5% of the femoral head diameter correlated with inferior clinical outcomes (modified Harris Hip Score) compared with the under-resected population.…”
Section: Discussionmentioning
confidence: 99%
“…documented to cause inferior clinical outcomes, 11 negatively affect hip joint biomechanics, 12 predispose to femoral neck fractures, [13][14][15] and produce a high conversion rate to total hip arthroplasty. 11 We present an arthroscopic surgical technique for achieving the perfectly spherical femoroplasty, meant to minimize complications using fluoroscopic guidance to confirm accuracy of resection, and ultimately improve postoperative patient outcomes. 11 Advantages, risks, and limitations for arthroscopic spherical femoroplasty are noted in Table 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An acetabuloplasty was performed to address pincer-type FAI and a femoroplasty was performed to address cam-type FAI. (16)(17)(18) Ligamentum teres (LT) tears were debrided; (19) full-thickness, chondral defects were addressed with microfracture; (20) and iliopsoas impingement lesions or painful internal snapping were treated with iliopsoas fractional lengthening. (21,22) Labral tears were treated with repair, debridement, resection, or reconstruction depending on the integrity of the labrum.…”
Section: Surgical Techniquementioning
confidence: 99%